Evaluasi Diagnostik Berbasis Asesmen Kognitif dan non-Kognitif pada Mata Pelajaran Pendidikan Kewarganegaraan - Muhammad Nurman (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2024)
This study aims to see the results of the implementation of cognitive and non-cognitive-based diagnostic assessments in civic education subjects at MTs. Lombok Timur. The method used in this study is a quantitative descriptive method. Data collection techniques include tests, questionnaires, observations, interviews, and documentation. Primary data sources were obtained from teachers and students, while secondary data were collected through analysis of diagnostic assessment implementation reports. Research data obtained through tests and questionnaires were analyzed and described with graphs depicting the number of students who obtained scores from the results of cognitive and non-cognitive diagnostic assessments. The results of the cognitive diagnostic assessment were obtained from a total of 130 students, 45 students who successfully obtained a score ≥ 70 and 85 students obtained a score < 70, and these results indicate that 65% of students have not reached the established graduation standards. The results of the non-cognitive diagnostic assessment regarding student learning style preferences include three main categories: 45 students have a visual learning style, 24 students show an auditory learning style, and 61 students have a kinesthetic learning style. 21% of students showed a very high interest in learning civics, 28% had a high interest, 48% had a low interest, and 3% had a very low interest. This data provides a clear picture of students' learning preferences, which can be used to design more engaging and relevant learning approaches.